2013
DOI: 10.1093/bja/aet061
|View full text |Cite
|
Sign up to set email alerts
|

Positive end-expiratory pressure aggravates left ventricular diastolic relaxation further in patients with pre-existing relaxation abnormality

Abstract: Increasing PEEP led to a progressive decline in LV relaxation in patients with pre-existing LV relaxation abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
(14 reference statements)
2
16
1
2
Order By: Relevance
“…We used "E" values for defining diastolic dysfunction in our study, as it is mostly independent of both preload and heart rate. It is well known that inotrope therapy may affect myocardial functions (34)(35)(36)(37)(38). More than 40% of the patients in their study were already on inotropes at the time of echocardiography compared to only 14% (eight of 56) in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…We used "E" values for defining diastolic dysfunction in our study, as it is mostly independent of both preload and heart rate. It is well known that inotrope therapy may affect myocardial functions (34)(35)(36)(37)(38). More than 40% of the patients in their study were already on inotropes at the time of echocardiography compared to only 14% (eight of 56) in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…PEEP may worsen myocardial perfusion. Recent study by Chin et al demonstrated that incremental PEEP from 0 cm H 2 O to 5 and 10 cm H 2 O worsened diastolic dysfunction in patients with preexisting diastolic dysfunction that might take the risk to myocardial infarction [12]. …”
Section: Pathophysiology Of Peepmentioning
confidence: 99%
“…The end‐diastolic dimensions of the LV decrease during positive pressure ventilation, and multiple factors may contribute to this. Positive pressure ventilation reduces right ventricular preload and this will, shortly after, reduce left ventricular filling pressure.…”
Section: Echocardiography During Positive Pressure Ventilationmentioning
confidence: 99%
“…If the pulmonary artery pressure is increased concomitantly, this effect on left ventricular filling will be exacerbated. The echocardiographic result is a decrease in both early diastolic transmitral flow (pulsed Doppler E‐wave) and of early relaxation velocities of the mitral valve annuli, e′ . In addition, interventricular interdependence may be of influence.…”
Section: Echocardiography During Positive Pressure Ventilationmentioning
confidence: 99%
See 1 more Smart Citation